Case report: Successful treatment of acute generalized pustular psoriasis of puerperium with secukinumab - Xue, Gao; Lili, Ma; Yimiao, Fang; Miao, Wu; Xiaohong, Yang; Dongmei, Wang (Frontiers in Medicine, 2022)
Generalized pustular psoriasis (GPP) is a rare and severe form of psoriasis presenting with erythematous, aseptic pustules. Common systemic symptoms include fever and myalgias. The presentation of GPP resembles acute generalized exanthematous pustulosis (AGEP). However, the treatment of these two pathologies differs. While AGEP is self-limiting and treated with topical corticosteroids and constrain of systemic steroids. GPP treatment avoids corticosteroid, choosing acitretin, methotrexate, and cyclosporine as first-line agents. In this case report, a 27-year-old female with a medical history of AGEP presented to the hospital with extensive erythema and pustules. Complete blood count acute phase reactant analysis revealed an elevated white blood cell count and C-reactive protein (CRP). Two histopathological examinations revealed psoriatic hyperplasia of the epidermis with keratosis, along with Kogoj and Munro micro abscesses above the spina layer. Lymphocytic and neutrophilic infiltrate was present in the superficial derma layer along with vasodilation. The patient was diagnosed with GPP according to pathological and clinical criteria. Treatment was initiated with secukinumab because of the patient’s failure to respond to systemic treatment with Acitretin, methotrexate, and cyclosporin. Following 2 weeks of therapy with 300 mg of secukinumab, the pustular lesions had resolved. This study indicates the potential efficacy of secukinumab as an effective therapy that can rapidly improve the clinical symptoms of GPP.